STUDY OF THE IMPACT OF MICRONUTRIENT FOUND IN SPERAMAX® DURING PREGNANCY PERIODS ON EMBRYONIC DEVELOPMENT AND NEWBORN - Hamzah, Sawsan S (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: This paper aims at evaluating the benefits of vitamins and minerals found in the Speramax® supplement and the risks to mother and infants of additional supplementation and possible adverse interactions between micronutrients in pregnancy. Method: A total of 30 male and 120 female albinos Swiss mice of 8–12 weeks of age weighing 25–35 g were used. Speramax was administrated orally for 1, 2, and 4 weeks. Fertile female mice were classified into four main groups: Group 1 is spontaneously (SPO); Group 2 is administrated with SperamaxÒ only; Group 3 is treated SperamaxÒ with superovulation (SUO); and Group 4 is superovulated only without Speramax. Result: The results indicated that treatment with Speramax® showed a positive effect on neonatal development and an increase in the number of newborn SPO and SUO treated with Speramax® after 1 week and 2 weeks. The results showed high significance (p˂0.000) compared with SPO and SUO mice not treated with Speramax® and with groups treated for 4 weeks. Conclusion: Good nutrition found in Speramax® may, therefore, be especially important to this group of infants and must be instituted alongside other nutritional supplements.